2006
DOI: 10.1093/nar/gkj015
|View full text |Cite
|
Sign up to set email alerts
|

CTGA: the database for genetic disorders in Arab populations

Abstract: The Arabs comprise a genetically heterogeneous group that resulted from the admixture of different populations throughout history. They share many common characteristics responsible for a considerable proportion of perinatal and neonatal mortalities. To this end, the Centre for Arab Genomic Studies (CAGS) launched a pilot project to construct the ‘Catalogue of Transmission Genetics in Arabs’ (CTGA) database for genetic disorders in Arabs. Information in CTGA is drawn from published research and mined hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 6 publications
2
51
0
Order By: Relevance
“…In fact, our findings reveal an increased risk of nearly six times for developing a recessive disorder. This result is consistent with a prior publication on genetic disorders in the Arab world which reported that consanguineous marriage increases the incidence of autosomal recessive disorders by five to ten times at the population level (Tadmouri et al 2006). In Tunisia, few studies have focused on inbreeding and its genetic consequences.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, our findings reveal an increased risk of nearly six times for developing a recessive disorder. This result is consistent with a prior publication on genetic disorders in the Arab world which reported that consanguineous marriage increases the incidence of autosomal recessive disorders by five to ten times at the population level (Tadmouri et al 2006). In Tunisia, few studies have focused on inbreeding and its genetic consequences.…”
Section: Resultssupporting
confidence: 93%
“…Likewise, a previous study conducted on a cohort of 100 Egyptian patients suffering from various recessive autosomal conditions reported that the frequency of consanguinity among parents of patients was significantly higher (p < 0.01) than that reported for the general Egyptian population (Mokhtar et al 1998). A previous report on genetic disorders in Arab countries shows that the majority of genetic conditions reported over the last decades among Arab populations are recessively inherited (Tadmouri et al 2006). This finding was recently confirmed by a study that aimed at assessing the burden of these inherited disorders on the Tunisian population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The incidence of genetic diseases is higher than in the developed world. As a matter of fact, several new genetic diseases were identified in Arabs.…”
Section: Jima: Volume 40 2008 -Page 98mentioning
confidence: 99%
“…The HGVS website displays two mutation databases dedicated to the Arab population, including the Catalogue of Transmission Genetics in Arabs (CTGA) Database, constructed by the Centre for Arab Genomic Studies, and The Lebanese National Mutation Frequency Database. 6,7 Morocco is located at the northwest of Africa with a land area of 710.850 km 2 . It is bordered in the north by the Mediterranean Sea, to the south by Mauritania, to the east by Algeria and to the west by the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%